Predictive Value of Dobutamine Stress Perfusion Echocardiography in Contemporary End‐Stage Liver Disease - Baibhav, Bipul (J Am Heart Assoc, 2017)
BACKGROUND: The assessment of cardiac risk in contemporary liver transplantation (LT) has required more sensitive testing for the detection of occult coronary artery disease as well as microvascular and functional cardiac abnormalities. Because dobutamine stress perfusion echocardiography provides an assessment of both regional systolic and diastolic function as well as microvascular perfusion (MVP), we sought to examine its incremental value in this setting. METHODS AND RESULTS: We evaluated the predictive value of dobutamine stress perfusion echocardiography in 296 adult patients with end‐stage liver disease and preserved systolic function who underwent LT between 2008 and 2014. The primary outcome was cardiovascular death, nonfatal myocardial infarction, and/or sustained ventricular arrhythmias following LT. The main causes of liver failure were hepatitis C (25%) and nonalcoholic fatty liver disease (13%). Abnormal MVP during stress was observed in 18 patients (6%), whereas diastolic dysfunction was present in 109 patients (94 grade 1, 15 grade 2). Half of the patients (7 of 14) referred for angiography with abnormal MVP had significant epicardial disease by angiography, and these patients were revascularized prior to LT. Despite these interventions, the primary outcome still occurred in 9 patients (3%). Patients with abnormal MVP during dobutamine stress perfusion echocardiography had a 7‐fold higher risk of a cardiovascular event following LT. Cox proportional hazards modeling examining clinical variables, left ventricular ejection fraction, diastolic function, and stress‐induced wall motion abnormalities or MVP defects demonstrated that abnormal MVP was the only independent predictor of the primary outcome (P=0.004; hazard ratio 7.7). CONCLUSIONS: Stress MVP assessments are highly predictive of cardiovascular outcome in current LT candidates.